Improving Mathematics Teaching Teacher Performance In Class On Learning Applications active Learning Method Joint Model Lectures And Group Work In Elementary Schools State 022 Tambusai - Tommi Sari (STKIP Rokania Pasir Pangaraian, 2022)
This study aims to improve the performance of teachers in teaching mathematics in the classroom by using the combined active learning method model of lectures and group work. This research was carried out in three cycles, because from the results of research and data analysis, it turned out that in the second cycle, teacher professionalism had increased, so this research was continued to cycle III to make it more perfect. From the results of this study, it can be concluded that to improve the professionalism of teachers in teaching and learning activities, it can be done by applying the effectiveness of teaching models and learning methods to teachers.